1998
DOI: 10.1094/pdis.1998.82.10.1107
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Phytoplasma-Associated Papaya Diseases in Queensland, Australia

Abstract: Three phytoplasma-related diseases of papaya (Carica papaya), dieback, yellow crinkle, and mosaic, are recognized within Australia. Immature leaf material was sampled every week for 8 months from a cohort of 60 female plants, located within a commercial papaya plantation, to determine the minimum time between infection and symptom expression. Phytoplasma DNA was detected using the polymerase chain reaction (PCR) with primers specific for phytoplasmas in general, and for the stolbur group of phytoplasmas. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 20 publications
1
11
0
2
Order By: Relevance
“…These findings confirm and extend earlier reports, which show phytoplasma infections lead to the accumulation of carbohydrates in source leaves (Lepka et al 1999;Bertamini et al 2002a;Maust et al 2003). It was reported that the sucrose contents in the sink organs of phytoplasma-infected plant, such as root, were lower than those in the healthy ones (Guthrie et al 1998). Therefore, there is an unresolved issue relating to the reason for which the infected plants cannot control the allocation of resources between source and sink organs at the whole-plant level.…”
Section: Phytoplasma Infection Affects Carbohydrate Transportion and supporting
confidence: 90%
See 1 more Smart Citation
“…These findings confirm and extend earlier reports, which show phytoplasma infections lead to the accumulation of carbohydrates in source leaves (Lepka et al 1999;Bertamini et al 2002a;Maust et al 2003). It was reported that the sucrose contents in the sink organs of phytoplasma-infected plant, such as root, were lower than those in the healthy ones (Guthrie et al 1998). Therefore, there is an unresolved issue relating to the reason for which the infected plants cannot control the allocation of resources between source and sink organs at the whole-plant level.…”
Section: Phytoplasma Infection Affects Carbohydrate Transportion and supporting
confidence: 90%
“…It was reported that the sucrose contents in the sink organs of phytoplasma‐infected plant, such as root, were lower than those in the healthy ones (Guthrie et al . ). Therefore, there is an unresolved issue relating to the reason for which the infected plants cannot control the allocation of resources between source and sink organs at the whole‐plant level.…”
Section: Discussionmentioning
confidence: 97%
“…The model originally proposed by Guthrie et al . 46 could be modified based on our results (Fig. 9).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which symptoms arise might be complex and could involve a number of different virulence strategies. The model originally proposed by Guthrie et al [46] could be modified based on our results ( Fig. 9).…”
Section: Occurrence Mechanism Of MDmentioning
confidence: 99%
“…Another pathway of phytoplasma survival and transmission is vegetative propagating plant material. As it mentioned phytoplasma invading phloem tissue and it is mostly find that in woody plants they disappear from aerial parts of trees during the winter and survive in the root system to recolonize the stem and branches in spring (149,150,58).…”
Section: Relevant Features Of Phytoplasmasmentioning
confidence: 99%